Tax avoidance, ethics, and corporate governance: A multinational study - Bajpai, Amardeep; Sonawane, Jayshree Dattatray; Aaradhi, Bhagyashri Rangnath; Patil, Laxman Arjun; Garg, Ram; Soumya, R (The International tax journal, 2026)
The paper is informed by evidence in different jurisdictions to explore how different governance structures and board structure, pattern of ownership and regulation structures in different jurisdictions contribute to the extent and nature of tax avoidance. Based on the analysis, coherent corporate governance practices such as independent boards, transparent reporting and productive oversight are bound to mitigate aggressive tax practices particularly in the environment in which there is intense ethical values and civic oversight. Conversely, weak systems of government are also likely to encourage predatory behaviours that are not conducive to long term sustainability but instead, minimisation of taxes. The theoretical knowledge of an agency theory, the stakeholder theory and the institutional theory combined provides the study with a holistic view of ethical and governance-related topics of tax avoidance. The findings contribute to the existing debates about corporate responsibility, global tax justice, and the role of policies regarding the governance that contributes to making the business correspond to the expectations of the society.